1992
DOI: 10.1258/002367792780745922
|View full text |Cite
|
Sign up to set email alerts
|

Sex ratio and mortality in a laboratory colony of the common marmoset (Callithrix jacchus)

Abstract: SummaryIn a retrospective study sex ratio and mortality were analysed in a captive colony of common marmosets (Callithrix jacchus). Seven hundred and thirty-five infants in 294 litters (20 singletons, 119 twins, 140 triplets, 14 quadruplets) out of 57 breeding females were evaluated. The sex ratio at birth was O· 95 males: 1· 0 females. The frequency of males and females, as well as the sex composition of twins and triplets confirm the assumption of dizygotic twinning in the common marmoset. According to age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 6 publications
(7 reference statements)
7
28
0
Order By: Relevance
“…The incidence of stillborns in our colony was more frequent in the first litter, as was also observed by Rothe et al [12], but we cannot associate it with birth weight of the infants because we do not have data for all the stillborn animals.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The incidence of stillborns in our colony was more frequent in the first litter, as was also observed by Rothe et al [12], but we cannot associate it with birth weight of the infants because we do not have data for all the stillborn animals.…”
Section: Discussionsupporting
confidence: 59%
“…These results disagree with those reported by Rothe et al [12] and Box and Hubrecht [13] but are closely similar to those observed by Phillips [14]. The higher proportion of triplets than twins in the first two studies was related to the high quality of food in captivity.…”
Section: Discussionsupporting
confidence: 47%
“…In a retrospective study of a colony of Callithrix jacchus, in 294 births a perinatal mortality rate of 20.6% was observed (ROTHE et al 1992). Richter (1984) cites 11 dystocias in 1,046 births of callitrichideos.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent data suggests that there is no such phenomenon either in the moose (Nygren & Kojala 1997), or the common marmoset (Rothe et al 1992). In contrast there has been confirmation of the suggestions in regard to the pig (Brooks et al 1991) and the mouse (Krackow 1992 a); and fresh data supporting the suggestion in the rat (Blumberg et al 1992;Hornig & McClintock 1997), the sheep (James 1976-though see Skjervold 1979, in some hamster litters (Clark et al 1991), the spotted hyena (Hofer & East 1997;James et al 1999) and in roe deer (Macdonald and Johnson 2008).…”
Section: The Empirical Evidencementioning
confidence: 93%